Measurement of differential cross sections for inclusive isolated-photon and photon+jets production in proton-proton collisions at $\sqrt{s} =$ 13 TeV - CMS collaboration (2299 authors) (2019)
Measurements of inclusive isolated-photon and photon+jets production in proton-proton collisions at $\sqrt{s} =$ 13 TeV are presented. The analysis uses data collected by the CMS experiment in 2015, corresponding to an integrated luminosity of 2.26 fb$^{-1}$. The cross section for inclusive isolated-photon production is measured as a function of the photon transverse energy, for $E_T>$ 190 GeV, and rapidity, for $|y|<$ 2.5. The cross section for photon+jets production is measured as a function of the photon transverse energy, for $E_T>$ 190 GeV, the photon rapidity, for $|y|<$ 2.5, and the rapidity of the jet with highest transverse momentum, up to $|y|<$ 2.4. The experimental measurements are found to be in agreement with predictions from perturbative QCD.